Epidemiology and clinical features of intraocular lymphoma in Singapore - Hah, Yan Yee; Ho, Su Ling; Teoh, Stephen Charn Beng; Agrawal, Rupesh (Nepalese Journal of Ophthalmology, 2019)
Introduction: Intraocular lymphoma is rare. There are very few studies on intraocular lymphoma published from Asian countries. Objective: To report our case series of intraocular lymphoma patients from a tertiary eye centre in Singapore. Subjects and methods: Nine patients with intraocular lymphoma managed between January 2005 and December 2014 were identified from Ocular Autoimmune Systemic Inflammatory Infectious Study (OASIS) database. Demographic characteristics, clinical presentation, investigations performed and outcomes recorded. Results: There were almost equal distribution between males (four patients) and females (five patients) with mean age of presentation was 60.3 years. Five patients had bilateral involvement and vitreo-retina was the most common site of infiltration. All of our patients had central nervous system involvement although four of them had presented with ocular manifestations initially. Anterior chamber fluid cytology, as a less invasive alternative to vitreous analysis was proven to be useful. The time from ocular presentation to diagnosis of ocular lymphoma was variable; from one day to 18 months. Mortality in our study group was 55% with death occurring 1 month to 8 years from diagnosis of intraocular lymphoma. Conclusion: Intraocular lymphoma is a masquerade syndrome that mimics chronicuveitis and poses a diagnostic challenge. The diagnosis is often delayed and despite the eventual diagnosis, the disease prognosis is poor even with aggressive treatment.